Misinterpretation of Arbitration Clauses in Sharia Economic Disputes: A Legal Analysis of Judex Facti Errors in Determining Judicial Competence (A Study of Supreme Court Decision Number 2460 K/Pdt/2010) - Abdullah Rasyid Lubis (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study aims to analyze the errors of the judex facti judge in interpreting the arbitration clause in a sharia economic dispute, with a case study of the Supreme Court Decision Number 2460 K/Pdt/2010 between Drs. Murni Anwar against PT Haman Rokko Enterprise and Bank Syariah Mandiri. The main focus of this study is the form of error of the District Court judge in determining judicial competence as well as the legal and epistemological implications of the error in interpreting the arbitration clause. This study uses a juridical-normative approach with an analysis of laws and regulations, legal doctrine, and court decisions. The results of the study indicate that the judge of the East Jakarta District Court has committed an error in competence because he interpreted the arbitration clause automatically eliminating the court's jurisdiction, even though the clause does not meet the formal requirements as stipulated in Article 9 paragraph (1) of Law Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution. In addition, the judge also committed a hermeneutic error, an interpretive error due to only understanding the arbitration clause textually without considering the context of Islamic economic law as stipulated in Article 55 of Law Number 21 of 2008 concerning Islamic Banking. This error indicates an epistemic dualism between positive law and Islamic law, where the judge still adheres to the positivistic paradigm and ignores the principle of maqasid al-syari‘ah which emphasizes substantive justice. The Supreme Court, through corrections at the cassation level, restored the balance between the principle of lex specialis derogat legi generali and the principle of substantive justice. This decision emphasizes the importance of hermeneutic and systematic legal interpretation in Islamic economic cases and emphasizes the role of the Religious Court as the primary institution in resolving Islamic economic disputes. This research contributes to the development of Islamic economic law enforcement theory by emphasizing the importance of harmonization between national procedural law and the principles of Islamic justice. This study also recommends the need to establish a jurisprudential doctrine regarding the validity of sharia arbitration clauses to ensure consistency in the application of the law and protection of the parties' rights to justice.